1996
DOI: 10.1046/j.1365-2141.1996.d01-1836.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange with solvent/detergent‐treated plasma of resistant thrombotic thrombocytopenic purpura

Abstract: A patient with unremitting thrombotic thrombocytopenic purpura (TTP), with circulating von Willebrand factor (VWF) multimers of unusually high molecular weight, and refractory to standard plasma exchange therapy, was treated with solvent detergent (S/D) plasma. The patient achieved a sustained clinical and haematological remission, with normal VWF multimeric profile. Spontaneous remission of this patient's condition could not be excluded but would appear unlikely. S/D plasma was efficacious and potentially saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…The occurrence of plasma-related allergic reactions due to the use of CPP and FFP are reported [23,24]. However, recent studies indicated a reduced risk of complications if SDP was used, even in patients who developed allergic reactions after the use of FFP [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence of plasma-related allergic reactions due to the use of CPP and FFP are reported [23,24]. However, recent studies indicated a reduced risk of complications if SDP was used, even in patients who developed allergic reactions after the use of FFP [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In common use are cryosupernatant (CPP) and fresh frozen plasma (FFP), but recently solvent/detergent-treated plasma (SDP) has increasingly been used [2,[18][19][20][21][22][23]. The occurrence of plasma-related allergic reactions due to the use of CPP and FFP are reported [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is an urgent need for plasma before such IgA-deficient plasma units can be collected, it may be more reasonable to transfuse SD-treated plasma slowly and under controlled conditions than to withhold treatment. SD-treated plasma is associated with fewer acute reactions than conventional plasma and has been used in selected patients who have not tolerated transfusions of conventional plasma without acute reactions [28]. SD-treated plasma has been transfused without complication in a patient with a history of anaphylactoid reactions to plasma-containing products who had IgA deficiency and antiIgA2 [6].…”
Section: Plasmamentioning
confidence: 99%